Design and Implementation of a Self-Calibration Paper Counting System Using Capacitive Sensing and Curve Fitting - Junyuan Zheng; Lei Chen; Xuxin Zhao; Ming Lei; Xiaoping Chen; Xiaochao Ma (IEEE Access)
This paper presents a novel self-calibrating paper counting device that integrates an embedded processor with a capacitance sensor chip. The device operates on the principle of capacitance measurement, detecting variations between two copper-coated plates as paper sheets are inserted. The capacitance data, acquired via an I2C interface, undergoes filtering and averaging to enhance stability and accuracy. Further processing involves scaling and transformation to refine the data, which is then utilized in curve fitting to determine the precise sheet count. The final result is displayed on an LCD screen, accompanied by an audible signal upon measurement completion. Experimental results demonstrate that the incorporation of data fusion and curve fitting significantly improves measurement accuracy, maintaining it consistently above 97%. This highlights the proposed system’s high precision and robustness, making it a promising solution for paper counting applications.